Photoactive nanocatalysts as DTT-assisted BSA-AuNCs with enhanced oxidase-mimicking ability for sensitive fluorometric detection of antioxidants - Swain, Sanskruti; Lin, Ting-Yi; Chou, I-Hsuan; Liu, Shu-Chen; Mallick, Bikash C.; Lin, Hsing-Ying; Huang, Chen-Han (Journal of nanobiotechnology, 2024)
Redox imbalance and oxidative stress are increasingly recognized as significant factors in health disorders such as neurodegenerative disorders, premature aging and cancer. However, detecting antioxidant levels that is crucial for managing oxidative stress, can be challenging due to existing assays' limitations, such as insensitivity to thiol-containing antioxidants. This study presents a simple fluorescence-based assay for antioxidant detection employing the enhanced photocatalytic oxidase-like activity of dithiothreitol (DTT)-assisted bovine serum albumin (BSA)-stabilized gold nanoclusters (DTT@BSA-AuNCs). The reported nanozyme exhibits remarkable stability, versatility, and catalytic activity. Under LED irradiation, DTT@BSA-AuNCs generate singlet oxygen, which converts non-fluorescent thiamine to fluorescent thiochrome, utilizing dissolved oxygen for catalysis. Antioxidants inhibit thiochrome formation, leading to fluorescence quenching. This method enables sensitive detection of antioxidants such as ascorbic acid and glutathione with limits of detection of 0.08 µM and 0.32 µM, respectively, under neutral pH, outperforming previous studies. The assay successfully detects antioxidants in human saliva and cancer cell models. The DTT@BSA-AuNCs-based assay offers a cost-effective, sensitive, and straightforward approach for detecting antioxidants in biological samples, facilitating improved monitoring of oxidative stress in various diseases.